Propaganda Fide dan Kebijakan Tentang Imam Diosesan di Wilayah Misi dalam Instruksi La Missione Universale - Alphonsus Tjatur Raharso; Henricus Pidyarto Gunawan (Litbang STFT Widya Sasana Malang, 2023)
Diocesan priests’ moving or transferring abroad - at any motives – will affect both positively or negatively to the diocese they leave. Human mobility which is supported by the nowadays advanced and varied transportation facilities, enabling the greater possibility of this mobility. This research is discussing on the instruction of the Propaganda Fide entitled La Missione Universale issued issued on April 25, 2001, which regulates the diocesan priests’ mobility. Through the legal research method, with a juridical-normative approach, this study aims to analyse the degree of legal synchronisation between the instruction and the laws above it. It also analyses the legal synchronisation between the instruction and its implementation at a lower level, namely the follow-up by the Italian Bishops' Conference in the form of agreement document. The research shows that the instruction is corresponding to the laws above it, and its implementation at the diocesan level is in line with the instruction above it. Previously, the moving abroad of a diocesan priest is seen from negative side of the disciplinary point of view only. The instruction now puts it positively in a broader context, that is, in the frame of missionary collaboration and communion among particular Churches. Inter-diocesan co-operation in the form of exchange of priests for a specific pastoral ministry is an effective means to carry out the missionary mandate of the Church. The inter-diocesan collaboration of the priest exchange for a special pastoral service is an effective means to undergo the mission of the Church.